Level of Knowledge Creation Process of Restaurants Setting in Catarman, Northern Samar - Matabia, Mabel (Journal of Interdisciplinary Perspectives, 2025)
This study focused on determining the level of knowledge creation among restaurants in Northern Samar, particularly in the municipality of Catarman, in terms of the SECI model (socialization, externalization, combination, and internalization). Utilizing a descriptive research design, the study surveyed 190 respondents from different restaurant settings in Catarman. Data were gathered using a validated survey questionnaire and statistically analyzed using a weighted mean. The results showed that among the four dimensions, socialization has the highest overall mean, followed by internalization, underscoring the restaurant’s commitment to nurturing a learning-oriented environment. The combination and externalization emphasize the importance of staff development, documentation, and brainstorming sessions that contribute to meaningful insights. The results reveal that the restaurant thrives on a strong culture of knowledge sharing, where staff are empowered not only to learn but also to contribute meaningfully to service innovation and organizational growth. These practices reflect a sustainable model for continuous improvement in the hospitality industry.